How Ordering of Assignments Can Influence Beliefs About the Self and How These Beliefs Can Impact on Student Class Performance - Ackerman, David S.; DeShields, Oscar (Alberta Journal of Educational Research, 2014)
This research examines whether the ordering of the difficulty of exams can influence student beliefs about their academic abilities and the impact of these beliefs on their performance. The ordering of the difficulty of test items has shown to affect performance. Study One (n=91) examined college student differences in reaction to a difficult and an easy exam. Results suggest that the ordering of difficulty of exams may influence self-efficacy of students. Study Two (n = 178) examines whether this self-efficacy (and other beliefs about the self) can impact college student performance on actual exam scores over time. The results of this research suggest that the ordering of difficulty of assignments can affect student’s self-efficacy about the class. It finds that the impact on self-efficacy may affect overall performance early in the class but that this impact may not be long lasting. This is due to the positive evidence received later in the course that may contradict initial low performance and give confidence in the student’s ability to achieve high performance. The results have implications for segments of the student population that may be disproportionately impacted by self-perceptions such as the first generation student. Cette recherche examine dans quelle mesure le classement des examens selon leur difficulté influence les croyances des étudiants par rapport à leurs habiletés académiques d’une part, et l’impact de ces croyances sur leur performance d’autre part. Il a été démontré que le classement des items d’un examen en fonction de leur difficulté a une incidence sur la performance. Étude #1 (n=91) porte sur les différences dans les réactions d’étudiants d’université à un examen difficile et à un examen facile. Les résultats portent à croire que l’ordre de présentation des examens selon leur difficulté peut influencer l’auto-efficacité des étudiants. Étude #2 (n=178) évalue dans quelle mesure cette auto-efficacité (et d’autres croyances relatives à soi) influence, à la longue, la performance aux examens des étudiants universitaires. Les résultats semblent indiquer que la présentation des examens en fonction de leur difficulté peut affecter la perception d’auto-efficacité chez les étudiants et que cet impact peut avoir des incidences sur la performance globale au début du cours mais que celles-ci peuvent être de courte durée. Ce phénomène s’explique par les indications positives qui peuvent venir contredire le faible rendement initial et rehausser la confiance des étudiants en leur capacité de bien réussir. Ces résultats comportent des implications touchant les secteurs de la population estudiantine qui pourraient être affectés de manière disproportionnée par leur image de soi, tels les étudiants de première génération.